2003
DOI: 10.1021/jp027830e
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl Naphthalene Reorientation at the Air−Liquid Interface upon Water Saturation Studied by Vibrational Broad Bandwidth Sum Frequency Generation Spectroscopy

Abstract: Vibrational broad bandwidth sum frequency generation spectroscopy was employed to investigate the surface structure of neat 1-methyl naphthalene (1-MN) and the reorientation of the 1-MN molecules upon saturation of the 1-MN liquid with water. The neat 1-MN liquid molecules have their aromatic rings aligned antiparallel to one another with their methyl groups alternating out of the surface and into the subsurface region from molecule to molecule. With the introduction of relatively few water molecules into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
(125 reference statements)
1
20
0
Order By: Relevance
“…No specific trends emerge in Figures and that distinguish chain length or branching, but we note that 1-methylnaphthalene (light blue, MN) lies below the prediction based on its high surface tension in Figure . This molecule, composed of two fused aromatic rings (Figure c), is observed to preferentially stack in a plane perpendicular to the surface. , It is intriguing to speculate that He atoms can pass more easily through gaps between the rigid rings than in spaces between flexible alkyl chains. This interfacial packing should be lost in the DO/SQ/MN mixture as the long-chain alkanes intermix with MN and because MN is depleted from the surface region.…”
Section: Discussionmentioning
confidence: 99%
“…No specific trends emerge in Figures and that distinguish chain length or branching, but we note that 1-methylnaphthalene (light blue, MN) lies below the prediction based on its high surface tension in Figure . This molecule, composed of two fused aromatic rings (Figure c), is observed to preferentially stack in a plane perpendicular to the surface. , It is intriguing to speculate that He atoms can pass more easily through gaps between the rigid rings than in spaces between flexible alkyl chains. This interfacial packing should be lost in the DO/SQ/MN mixture as the long-chain alkanes intermix with MN and because MN is depleted from the surface region.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Shen and co-workers used SFG to study the neat methanol liquid interface, and in 1993, they reported the first SFG spectrum of the pure water interface . Currently, SFG is the only technique capable of selectively producing vibrational spectra of neat liquid interfaces, liquid/air solution interfaces, or buried liquid/liquid interfaces. , …”
Section: Sum Frequency Generationmentioning
confidence: 99%
“…16 Currently, SFG is the only technique capable of selectively producing vibrational spectra of neat liquid interfaces, liquid/air solution interfaces, or buried liquid/liquid interfaces. 1,[17][18][19][20][21][22] The basis for SFG is as follows. When a light beam impinges on a surface, it induces a polarization by exerting a force on the valence electrons.…”
Section: Sum Frequency Generationmentioning
confidence: 99%
“…The first factor might be investigated in greater detail with atomistic simulations and surface sensitive spectroscopy (33), whereas a number of new experimental methods are available to probe dynamics at the surface of glasses (25,34). Structure at liquid surfaces is an active area of study (35,36), and our results indicate that physical vapor deposition might be a useful tool in this endeavor.…”
mentioning
confidence: 92%